Different Approach Analysis for Static Code in Software Development - Sudheer, N; Hrushikesava Raju, S (International Journal of Computer Sciences and Engineering, 2025)
Static analysis examines program code and reasons over all possible behaviors that might arise at run time. Tools based on static analysis can be used to find defects in programs. Recent technology advances has brought forward tools that do deeper analyses that discover more defects and produce a limited amount of false warnings. The aim of this work is to succinctly describe static code analysis, its features and potential, giving an overview of the concepts and technologies behind this type of approach to software development as well as the tools that enable the usage of code reviewing tools to aid programmers in the development of applications, thus being able to improve the code and correct errors before an actual execution of the code.